Quantitative REM Sleep without Atonia in Parkinson's Disease and Essential Tremor - Gossard, Thomas R. (Mov Disord Clin Pract, 2020)
BACKGROUND: Rapid eye movement (REM) sleep behavior disorder (RBD) occurs occasionally in essential tremor (ET), but polysomnographic REM sleep without atonia (RSWA) analyses have been sparse. OBJECTIVE: To characterize the amount and distribution of polysomnographic RSWA, the electrophysiologic substrate of RBD, in patients with Parkinson's disease (PD) and ET. METHODS: We analyzed quantitative RSWA in 73 patients: PD (23), ET (23), and age‐sex‐matched controls (27). None had dream‐enactment behavior history or received antidepressants. Phasic, tonic, “any,” and phasic‐burst duration RSWA measures were calculated in the submentalis (SM) and anterior tibialis (AT) muscles. The automated REM atonia index (RAI) was also determined. Statistical analysis was performed by Kruskal‐Wallis rank‐sum and Mann‐Whitney tests. RESULTS: SM phasic RSWA was significantly greater for PD than ET patients and controls (12.5% ± 12.8% vs. 4.9% ± 6.7%, 3.9% ± 2.6%), as was SM “any” (13.54% ± 14.30% vs. 5.2% ± 7.6%, 4.2% ± 2.6%). RAI was significantly lower in PD than in ET and controls (0.78 ± 0.23 vs. 0.92 ± 0.09 vs. 0.90 ± 0.17, P ≤ 0.005), but no different between ET and controls. AT phasic and “any” RSWA was similar between the 3 groups. ET and control RSWA was similar in all measures. Two ET patients (8.7%) had SM RSWA similar to PD patients. CONCLUSIONS: Elevated SM RSWA distinguished PD from ET in patients without dream‐enactment symptoms and occurs frequently in PD patients, and in isolated tremor suggests underlying synucleinopathy. Prospective studies will further validate these findings.